Déficit hídrico na eficiência de herbicidas e nas características bioquímicas de Euphorbia heterophylla - Dos Santos Vitorino, Hermeson [UNESP]; Martins, Dagoberto [UNESP]; De Almeida Costa, Saulo Ítalo [UNESP]; De Souza, Guilherme Sasso Ferreira [UNESP]; De Campos, Caio Ferraz [UNESP] (Universidade Estadual de Londrina, 2013)
The objective of this work was to evaluate conditions the effectiveness of acetolactate synthase (ALS) and protoporphyrinogen oxidase (PROTOX) inhibitors in the Bidens pilosa control under two water deficit conditions, as well as to determine the action under the content of soluble carbohydrates and protein and free amino acids of weed. The experimental design was randomized completely design, with four replications, with the treatments setup in a factorial scheme 4x2, with four herbicides (fomesafen lactofen, chlorimuron-ethyl and imazethapyr), and two soil water conditions (-0.5 MPa and -0.01MPa). At 7, 14, 21 and 28 days after application (DAA), was assessed visually control efficiency of herbicides. For the determination of organic solutes plants were collected at 24, 48, 72 and 96 hours after application (HAA), except for the amino acids were analyzed 48, 72 e 96 HAA. Herbicides fomesafen and lactofen were efficient to control E. heterophylla, while the ALS inhibitors (chlorimuron-ethyl e imazethapyr) provided an unsatisfactory control. Water deficit altered the efficiency of herbicides, mainly chlorimuronethyl. Lactofen provided a smaller content of soluble carbohydrates, in the same way, the protein ranged in the 72 HAA, the lower value observed for imazethapyr e lactofen respectively. Herbicide lactofen increased the concentration of free amino acids, while the imposition of water deficit caused an increase in soluble carbohydrate content.
Water stress on the performace of herbicides and biochemical characteristics of Euphorbia heterophylla
Keywords: Amino acids; Carbohydrates; Protein; Water stress; Wild poinsettia